Peran Unit Pelaksana Teknis Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Bandar Lampung dalam Penanganan Kasus Terkait Perempuan dan Anak (Studi Penelitian pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Bandar Lampung) - Rizki Agip Saputra; Lintje Anna Marpaung; Yulia Hesti (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
Based on the regulation of the mayor of Bandar Lampung Number 6 of 2020, the technical implementation unit for the protection of women and children was farmed to provide protection for women and children in Bandar Lampung city. This study uses a normative juridical method, and an empirical approach. The problem that will be discussed in this research is how the role of the technical implementation unit of the department of womens empowerment and child protection in Bandar lampung city in handling cases and what are the inhibiting factors. The results of the study indicate that the role of the technical implementing unit is to provide services for women and children who experience violence, discrimination, special protection, and other problems